Description of Baseline Characteristics of Pediatric Allergic Asthma Patients Including those Initiated on Omalizumab. (April 2018) - Kavati, Abhishek; Pilon, Dominic; Ortiz, Benjamin; Paknis, Brandee; Vegesna, Ashok; Schiffman, Bradd; Zhdanava, Maryia; Lefebvre, Patrick; Stone, Brian
Background: Indication of omalizumab in the United States was recently extended to include pediatric (6–11 years) uncontrolled moderate-to-severe allergic asthma patients. Objective: The purpose of this study was to describe baseline characteristics of this population from a real-world dataset. Methods: Allergic asthma patients and uncontrolled moderate-to-severe allergic asthma patients, aged 6–11 years, were identified in the Allergy Partners Network Electronic Medical Records (2007–2016). The index date for allergic asthma patients was the latest between the second asthma-related visit and the allergic status confirmation. Uncontrolled moderate-to-severe allergic asthma patients were stratified into omalizumab-exposed (index date) or omalizumab-unexposed (index date randomly generated) groups. Characteristics were evaluated during the 12-month preindex period. Results: A total of 5806 allergic asthma, 37 omalizumab-exposed, and 2620 omalizumab-unexposed patients were selected (mean age approximately 9 years). Allergic asthma and omalizumab-unexposed patients were predominantly white (70.2% and 61.2%) whereas the majority of omalizumab-exposed were African Americans (62.2%). Mean immunoglobulin E was 782.0 IU/ml in allergic asthma patients (available in 2.2%), 1134.4 IU/ml in omalizumab-exposed (available in 100.0%), and 746.1 IU/ml in omalizumab-unexposed (available in 3.1%). Allergic asthma patients were less severe than omalizumab-exposed and omalizumab-unexposed based on the forced expiratory volume in 1 s as a percentage of predicted value (FEV1 % predicted) and the Childhood Asthma Control Test (C-ACT). FEV1 % predicted was below normal (<80%) in 42.4% of omalizumab-exposed and 39.1% of omalizumab-unexposed patients, also 63.6% of omalizumab-exposed and 46.7% of omalizumab-unexposed had uncontrolled asthma (C-ACT score <20). In African American omalizumab-exposed patients, FEV1 % predicted was below normal in 47.6% and 55.0% had uncontrolled asthma. Conclusions: In a real-world setting, pediatric patients with uncontrolled moderate-to-severe allergic asthma have a significant disease burden as shown by high rates of poor lung function, disease control, and symptoms. Currently available treatments could help improve disease management in this population.